2020
DOI: 10.1177/1055665620984349
|View full text |Cite
|
Sign up to set email alerts
|

Skin Deep: Perception of Scars After Cranial Vault Reconstruction

Abstract: Purpose: Children with craniosynostosis are vulnerable to stigmatization and social withdrawal. Cranial vault reconstruction (CVR) results in large bicoronal scars, which may trigger further insult to self-esteem and social outcasting. This study aimed to delineate determinants of patient scar self-consciousness, parental scar satisfaction, and parent satisfaction with their child’s overall medical/surgical care. Methods: A 14-item questionnaire was distributed to parents of 95 patients who underwent open CVR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…We did not find an association between patient gender and mean POSAS or EQ-5D scores. This is consistent with previous scar satisfaction literature [ 8 , 14 - 16 ] and contradicts widely held gender stereotypes. It is important that physicians are aware of this to avoid male patients with scar concerns being overlooked.…”
Section: Discussionsupporting
confidence: 92%
“…We did not find an association between patient gender and mean POSAS or EQ-5D scores. This is consistent with previous scar satisfaction literature [ 8 , 14 - 16 ] and contradicts widely held gender stereotypes. It is important that physicians are aware of this to avoid male patients with scar concerns being overlooked.…”
Section: Discussionsupporting
confidence: 92%
“…As in previous reports, parents in our OCVR group felt that the zig-zag bicoronal scar was a source of stigma, especially in boys with short hair where it was more visible. 24 Given that metopic craniosynostosis is diagnosed in boys over three times more often than in girls, this should influence the choice of surgical technique. 25 This study is the first to recruit adolescents to assess aesthetic outcomes in patients with craniosynostosis.…”
Section: Discussionmentioning
confidence: 99%
“…4,8,15,30 In addition, failure to improve the cosmetic aspect can result in abnormal psychosocial development during childhood and adolescence which can ultimately lead to anxiety, self-consciousness, and depression. 20,23 Therefore, children with both syndromic and nonsyndromic craniosynostosis should have developmental, behavioral, and mental health support from the time of diagnosis. 31 These substantial and far-reaching consequences underline the importance of providing data related to prevalence of craniosynostosis and specific suture type among various ethnicities of patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that White patients receive surgery to repair craniosynostosis at an earlier age than non-White patients 4 . Roy et al 23 found that the mean age for surgery in White children was 7.2 and 9.1 months in African American and Hispanic children. Shweikeh et al 4 found that White patients had an average age of 6.1 months at the time of surgery, African American patients had a mean age of 10.9 months and Hispanics had a mean age of 9.1 months.…”
Section: Discussionmentioning
confidence: 99%